2018
DOI: 10.1016/j.ejrad.2017.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic patterns of osteoporotic proximal humerus fractures

Abstract: Osteoporosis of the proximal humerus was identified in 72% of patients during a two year period; most of these patients were elderly females sustaining low energy trauma. These fractures showed to have specific radiographic patterns, as comminution of metaphysis and tuberosities, impaction of fragments, and inferior subluxation of the humeral head. These patterns can be assessed with the simple observation of a 2-plan view of a radiograph, without the use of specific software.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…In fact, traumas, in both periods, occurred in the home environment and acted on an osteoporotic bone. The data seem to be in line with the results of Carbone et al, 7 who observed that 72% of patients with humeral head fractures were markedly osteoporotic and that most of these patients were elderly women sustaining low-energy trauma. Postacchini et al 20 in an epidemiologic study observed that clavicle fractures represent 2.6% of all fractures and that traffic accidents, falls, and sports injury were the most common causes responsible for the fracture.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, traumas, in both periods, occurred in the home environment and acted on an osteoporotic bone. The data seem to be in line with the results of Carbone et al, 7 who observed that 72% of patients with humeral head fractures were markedly osteoporotic and that most of these patients were elderly women sustaining low-energy trauma. Postacchini et al 20 in an epidemiologic study observed that clavicle fractures represent 2.6% of all fractures and that traffic accidents, falls, and sports injury were the most common causes responsible for the fracture.…”
Section: Discussionsupporting
confidence: 91%
“…New approaches will therefore be necessary in the future when it comes to osteoporotic patients. 4,5…”
Section: Introductionmentioning
confidence: 99%
“…New approaches will therefore be necessary in the future when it comes to osteoporotic patients. 4,5 PHF are more commonly observed in older women following low-energy trauma, and exhibit a specific radiological pattern. They manifest with metaphyseal and tubercle fragmentation, impacted fragments, and inferior subluxation of the humeral head.…”
Section: Introductionmentioning
confidence: 99%
“…This, in turn, should yield stronger correlations with fracture load, which will help develop advanced algorithms for proximal humerus fracture fixation and arthroplasty. 8,20,21…”
Section: Discussionmentioning
confidence: 99%
“…Determining whether these variables scale proportionally with bone length is important because the measurements of CI and MCCT could be made at the same percentage of total HL regardless of the size of the bone, which is an important step in advancing algorithms that guide treatment in proximal humerus fractures. 8,20,21 Accordingly, we asked: (1) Does HHD (from the CFM), Tingart distance, and Mather distance correlate with humerus length? (2) And if they do correlate, then what is the location of HHD, Tingart distance, and Mather distance as a percentage of humerus length?…”
Section: Introductionmentioning
confidence: 99%